2011
DOI: 10.1016/j.phrs.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

(R)-α-Lipoic acid treatment restores ceramide balance in aging rat cardiac mitochondria

Abstract: Inflammation results in heightened mitochondrial ceramide levels, which cause electron transport chain dysfunction, elevates reactive oxygen species, and increases apoptosis. As mitochondria in aged hearts also display many of these characteristics, we hypothesized that mitochondrial decay stems partly from an age-related ceramidosis that heretofore has not been recognized for the heart. Intact mitochondria or their purified inner membranes (IMM) were isolated from young (4-6 mo) and old (26-28 mo) rats and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 69 publications
3
22
0
1
Order By: Relevance
“…In addition, several alterations of the complex III holo-protein result in its lower activity, particularly in post-mitotic tissues of aging rodents [2, 4, 69, 71] and primates [72]. These results agree with other studies showing that defects of complex IV correlate with lower mitochondrial oxidative capacity in post-mitotic tissues of elder humans [73, 74], primates [72, 75], and rodents [3, 43, 76-79]. …”
Section: Age-associated Changes Of the Mitochondrial Energy Transdsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, several alterations of the complex III holo-protein result in its lower activity, particularly in post-mitotic tissues of aging rodents [2, 4, 69, 71] and primates [72]. These results agree with other studies showing that defects of complex IV correlate with lower mitochondrial oxidative capacity in post-mitotic tissues of elder humans [73, 74], primates [72, 75], and rodents [3, 43, 76-79]. …”
Section: Age-associated Changes Of the Mitochondrial Energy Transdsupporting
confidence: 87%
“…Cholesterol accumulates in the IMM, alters membrane fluidity, and may promote greater H + leakage [7, 91]. In a similar vein, using LC-MS/MS analysis, we recently demonstrated that aged cardiac mitochondria accumulate ceramide, a pro-apoptotic sphingolipid, which results in inhibition of complex IV activity [79]. Furthermore, three ceramide isoforms in the IMM (e.g.…”
Section: Age-associated Changes Of the Mitochondrial Energy Transdmentioning
confidence: 99%
“…It seems that ceramides with various chain lengths can be generated in a specifi c manner and have distinct bioactivities ( 50 ). The effects of aging on the FA composition of ceramide have been investigated in several models including mouse CD4+ T-cells ( 51 ), cardiomyocytes ( 52 ), and skeletal muscle ( 53 ). Our mass spectrometry-based analysis of ceramide species in the livers of aged and young mice reveals that aging leads to the accumulation of C16:0 and C24:1 ceramides and has no effect on the less abundant C18:0, C18:1, and C24:0 ceramides, while the level of C20:0 ceramide is modestly suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…There is a diverse localization of alkaline ceramidases: ACER1 is localized to the ER and is mainly expressed in the skin, ACER2 is localized to the Golgi, and ACER3 is localized to both the Golgi and ER. Although NCDase was thought to preferentially localize to the plasma membrane, accumulating evidence demonstrates the presence of NCDase activity, or the enzyme itself (depending on the tissue/cell studied), in endosomal/lysosomal compartments ( 57 ) and mitochondria (9)(10)(11)58 ). In our previous studies, we have shown that mitochondria-resident NCDase modulates the ceramide profi le of liver mitochondria ( 9 ).…”
Section: Increased Ceramide Hydrolysis By Ncdase Counterbalances De Nmentioning
confidence: 99%